Using flat phosphor layer in dual-layer remote phosphor configuration to improve luminous efficacy - My Hanh Nguyen Thi; Phung Ton That; Tri-Vien Vu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The phosphor layer shape and components distances are the subjects proposed to advance the quality of WLEDs in this article. The two distances, between phosphor layers (d1) and between the phosphor layer and the LED chip (d2) in Flat dual-remote phosphor (FDRP) and Concave dual-remote phosphor (CDRP) were examined by experiments to determine their impacts on WLEDs lighting performances. The results suggest that FDRP is a better option than CDRP for lighting performance. In each respective structure, the distances influence the lighting capacity and color output whenever they fluctuate. Therefore, to effectively control and study this phenomenon, the correlated color temperature is maintained at 8500 K, and the concentration of phosphor material is altered while the distances are changing. When d1 and d2 are at the starting value of 0, the recorded lumen output and chromatic performance of lighting devices are the lowest and begin to increase as d1 and d2 expand. Bigger d1 and d2 mean bigger scattering area and better chromatic light integration, which leads to higher color quality. Detailed results present that optimal values of d1 or d2 for the highest lumen output of 1020 lm are 0.08 mm or 0.63 mm, respectively. Meanwhile the lowest color deviation is accomplished with d1=0.64 mm or d2=1.35 mm.